The Implementation of Maqashid Shariah in the Resolution of Islamic Economic Disputes A Normative Juridical Analysis - Nilfatri; Alisyah Pitri (CV. Zabags Qu Publish, 2026)
The implementation of Maqashid al-Shariah in the resolution of Islamic economic disputes is essential to ensure that dispute settlement not only complies with formal legal provisions but also reflects the fundamental objectives of Islamic law. This study aims to examine the application of Maqashid al-Shariah in resolving Islamic economic disputes from a normative juridical perspective. The research employs a library research method by analyzing primary and secondary legal sources, including statutory regulations, Islamic legal principles, scholarly literature, and relevant academic studies. The analysis focuses on the extent to which the objectives of Maqashid al-Shariah, particularly the protection of religion (hifz al-din), life (hifz al-nafs), intellect (hifz al-'aql), lineage (hifz al-nasl), and property (hifz al-mal), can serve as substantive foundations for dispute resolution. The findings indicate that the principles of Maqashid al-Shariah provide a comprehensive framework for achieving justice, legal certainty, social benefit, and the protection of the parties' rights and interests. Its implementation can strengthen the resolution of Islamic economic disputes by encouraging equitable outcomes, preventing harm, and promoting mutual benefit (maslahah). Therefore, integrating Maqashid al-Shariah into the normative framework of Islamic economic dispute resolution is relevant to developing a legal system that is not merely procedural but also oriented toward substantive justice and the realization of public welfare.